2005
DOI: 10.1111/j.1525-1438.2005.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of spirituality and spiritual coping to anxiety and depression in women with a recent diagnosis of gynecological cancer

Abstract: The objective of this study was to determine whether, after accounting for illness and demographic variables, spiritual involvement and beliefs and positive and negative spiritual coping could account for any of the variation in anxiety and depression among women within 1 year's diagnosis of gynecological cancer (GC). One hundred patients from outpatient GC clinics at two Melbourne-based hospitals completed a brief structured interview and self-report measures of anxiety, depression, spirituality, and spiritua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
78
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 38 publications
3
78
1
5
Order By: Relevance
“…Two good studies [16,17] and one average study [27] found no differences between patients with ovarian cancer and those with other types of gynaecologic cancers. However, one good study [25] found that women with ovarian cancer experienced lower levels of depressive symptoms than those with cervical and endometrial cancer.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Two good studies [16,17] and one average study [27] found no differences between patients with ovarian cancer and those with other types of gynaecologic cancers. However, one good study [25] found that women with ovarian cancer experienced lower levels of depressive symptoms than those with cervical and endometrial cancer.…”
Section: Resultsmentioning
confidence: 95%
“…From these findings, it was concluded that there is strong evidence for a relationship between increased levels of physical symptoms and increased levels of psychological distress. Phase of treatment (active/follow-up) was not associated with levels of depression/anxiety in the one good study that addressed this issue [16]. In addition, no differences in psychological distress were found between those with newly diagnosed and recurrent cancer in one average study [20], suggesting that both cancer phases are psychologically equally difficult.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations